1993
DOI: 10.1029/93ja00604
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic simulations of the Kelvin‐Helmholtz instability at the magnetopause

Abstract: Two-dimensional hybrid simulations with particle ions and fluid electrons are used to calculate the kinetic evolution of the Kelvin-Itelmholtz instability for a magnetopauselike configuration. The unidirectional magnetic field is essentially transverse to the plasma flow velocity, which is the most unstable case according to linear theory and models the flow dynamics in the subsolar region of the magnetopause for northward interplanetary magnetic field. We recover effects analogous to those found in MHD simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 55 publications
10
92
1
Order By: Relevance
“…These studies find results similar to those of MHD but often with structures breaking off of irregular vortices [e.g., Thomas and Winske, 1993]. The focus of these studies is on mixing of magnetosphere and magnetosheath plasmas.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…These studies find results similar to those of MHD but often with structures breaking off of irregular vortices [e.g., Thomas and Winske, 1993]. The focus of these studies is on mixing of magnetosphere and magnetosheath plasmas.…”
Section: Introductionmentioning
confidence: 80%
“…Maximum mixing is often found in the simple, but unrealistic, case of uniform density and field across the velocity shear. Thomas and Winske [1993] find that a density change across the boundary suppresses vortex development and mixing, whereas Matsumoto and Hoshino [2006] find larger density changes leads to secondary instabilities and increased mixing. Fujimoto and Terasawa [1995] find that a B magnitude change across the boundary decreases mixing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the diffusion term due to the scattering of particles by the electric field (its non-electrostatic component) evolves as the square root of time. Thomas and Winske (1993) also used 2D hybrid simulations to put forward the inverse cascade (to longer wavelength) found in MHD and showed the existence of a small-scale structure (on the order of the ion larmor radius) that could be connected to flux transfer events or flux ropes. Two-dimensional Hybrid simulations used by Fujimoto and Terasawa (1994) showed that a large-scale mixing area develops at the corrugated interface.…”
Section: The Kelvin-helmholtz Instabilitymentioning
confidence: 99%